Novel GlyT1 inhibitor chemotypes by scaffold hopping. Part 1. Development of a potent and CNS penetrant [3.1.0]-based lead - Jones, Carrie K. (2014)
This letter describes the development and SAR of a novel series of GlyT1 inhibitors derived from a scaffold hopping approach that provided a robust intellectual property position, in lieu of a traditional, expensive HTS campaign. Members within this new [3.1.0]-based series displayed excellent GlyT1 potency, selectivity, free fraction, CNS penetration and efficacy in a preclinical model of schizophrenia (prepulse inhibition).